Meditations on first philosophy in focus - Descartes, René, 1596-1650.; Tweyman, Stanley, 1942-; Haldane, Elizabeth Sanderson, 1862-1937.; Ross, G. R. T. (George Robert Thomson) (London ; New York : Routledge, 1993)
This includes the excellent translation by Haldane and Ross of Descartes' Meditations on First Philosophy, an introduction by Tweyman, and six articles indicating the diversity of scholarly opinion on method in Descartes' philosophy.
Introduction -- Meditations on first philosophy -- Excerpt from Replies to objections II.
"Contains the excellent and popular Elizabeth S. Haldane and G.R.T. Ross translation."
Includes bibliographical references (pages 200-220) and index.
Print version record.
Contains the Elizabeth S. Haldane and G.R.T. Ross translation.
eBooks on EBSCOhost
Keywords: Descartes, René, -- 1596-1650 -- Et la méthodologie.; First philosophy; Methodology; Knowledge, Theory of; Metaphysics; Methods; Métaphysique -- Ouvrages avant 1800.; Dieu -- Existence -- Preuve ontologique -- Ouvrages avant 1800.; Méthodologie.; Théorie de la connaissance; Métaphysique.; metaphysics; methodology; epistemology; PHILOSOPHY -- History & Surveys -- Modern; First philosophy; Meditationes de prima philosophia (Descartes); Philosophy; France; Electronic books; Early works